Pulsed Radiofrequency and Platelet Rich Plasma in Degenerative Joint Arthritis: Two Case Reports and Literature Analyses - Luca Gregorio Giaccari; Francesco Coppolino; Caterina Aurilio; Maria Caterina Pace; Maria Beatrice Passavanti; Vincenzo Pota; Dario Alicino; Giuseppe Pulito; Pasquale Sansone (Life, 2023)
(1) Background: Osteoarthritis (OA) is a debilitating joint disease. The are several therapies available for OA. According to current knowledge, the combination of Platelet-Rich Plasma (PRP) and Pulsed Radiofrequency (PRF) can be applied in the treatment of pain of nociceptive origin due to peripheral tissue damage. (2) Methods: We performed a narrative review identifying the articles by searching electronic databases. A retrospective analysis of patients with OA treated with PRF and PRP in “Vito Fazzi” Hospital (Lecce, Italy) was performed. (3) Results: A total of four publications on the use of PRP and PRF in degenerative joint arthritis were included in our review. In our experience, two patients with OA were treated with PRP and PRF after unsuccessful conservative treatment. Patient pain score, daily activity ability, active range of activity, and muscle strength improved after treatment. Patients reported a higher level of satisfaction. No major adverse events were reported. (4) Conclusions: The goal of the combined application of the two treatments is to make full use of the analgesic effect of PRF and the repairing effect of PRP. At present, the therapeutic potential of PRP and PRF in OA remains unmet.